Stress-related cardiomyopathy due to anaphylaxis to iodinated contrast media during arteriography procedures in diabetic patient - Suryana, Ketut; Yudha Kartika, I Gede (International Journal of Research in Medical Sciences, 2022)
Anaphylaxis is an acute, severe systemic allergic reaction that can be potentially fatal. It can often transition to refractory hemodynamic instability (new onset myocardial dysfunction/ left ventricular dysfunction/LVD). Stress-related cardiomyopathy (SRC) is now emerging as a significant contributor of myocardial dysfunction and has multifactorial etiologies, including the excessive catecholamine released in intense stress conditions. It is also more likely to occur in middle aged/ postmenopausal woman. This rare case report, a SRC caused by contrast-induced anaphylaxis within 30 minutes post artheriography procedures. Management of anaphylaxis should be prompt and precise because it is considered as a medical emergency with a rapid onset of disease and potentially progress to cardiovascular and respiratory collapse causing death.